James Benning : decoding fear - Pakesch, Peter; Steinbrügge, Bettina; Benning, James, 1942-; Kunsthaus Graz; Kunstverein in Hamburg (Köln : Verlag der Buchhandlung Walther König, 2014)
"The American artist and filmmaker James Benning focuses on the ambivalence that exists between technical progress and the promise of liberty in a culture still bound to its pioneering spirit. His work resonates with a critique of the information society and also an examination of recent US history: specifically of philosopher Henry David Thoreau (1817-1862) and mathematician Theodor Kaczynski (*1942). Between 1978 and 1995 the latter became know as the 'Unabomber'. All in all the publication shows the importance of this director's themes, his work so seemingly timeless, for our life today, shaped as it is by technical possibilities both positive and negative. Including texts by Diedrich Diederichsen, Tanja Vrvilo and a conversation between James Benning and Allan MacInnis."--Inside front cover.
Vorwort / Peter Pakesch, Bettina Steinbrügge -- James Benning : Romantik und Aufklärung / Diedrich Diederichsen -- James Benning : Erinnerungen aus den Händen / Tanja Vrvilo -- James Benning, der Unabomber und Stemple Pass : ein Interview / Allan MacInnis -- Anhang -- Werke der Ausstellung = Works in the exhibition -- Installationsansichten Kunsthaus Graz = Installation views Kunsthaus Graz -- Forward / Peter Pakesch, Bettina Steinbrügge -- James Benning : romanticism and enlightenment / Diedrich Diederichsen -- James Benning : memories from the hands / Tanja Vrvilo -- James Benning, the Unabomber, and "Stemple Pass" : an interview / Allan MacInnis -- Appendix -- Dokumente = Documents.
Title from cover.
Catalog published on the occasion of the exhibition "James Benning: Decoding Fear," Kunsthaus Graz, Universalmuseum, Joannenum, Graz, March 7-June 1, 2014 and Kunstverein in Hamburg January 24-March 22, 2015.
In German with English translation.
boek
Keywords: Benning, James; Verenigde Staten van Amerika